A mini hallux neurovascular osteo-onychocutaneous free flap for refined reconstruction of distal defects in thumbs and fingers. Issue 1 (28th February 2023) - Zhou, Xianyu; Sun, Di; Liu, Fei; Li, Wen Jun; Gu, Chuan; Zhang, Ling Ling
Abstract: Distal injury in thumbs and fingers is common in emergency. Although multiple surgical techniques have been introduced for repair purpose, it is still challenging for restoring both good function and cosmetic appearance. The present study reports our experiences on how to reconstruct amputated fingertips in thumbs and fingers using a mini hallux neurovascular osteo-onychocutaneous free flap with favorable outcomes in 15 patients (average age, 27.27 ± 5.43 years old). Follow-up period was 19.47 ± 10.18 months (range, 6–48 months). Digital function was improved indicated by the static two-point discrimination (2-PD) and key-pinch, which were 8.40 ± 1.64 mm (range, 6–12 mm) and 85.37 ± 3.03% (range, 80.2–90.6%) of that of the intact contralateral thumbs and fingers, respectively, after surgery. As to aesthetic outcomes, all reconstructed digits were self-graded as good by patients. 73.3% of the donor halluces were self-graded as good and four halluces (26.7%) were graded as fair . In conclusion, the mini hallux neurovascular osteo-onychocutaneous flap may be used for refined reconstruction of type I amputated injury in thumbs and fingers achieving both satisfactory functional and aesthetic outcomes.